83 How do medical students view leadership? A national curriculum analysis and survey. (12th November 2018) - Maskell, Katherine; Gibb, Jonathan; Devine, Oliver
Abstract : This project, conducted by the FMLM Medical Student Group, was the first national analysis of UK medical students' access to medical leadership and management (MLM) teaching, within the undergraduate curriculum, and their opinions regarding this. Timetables (2014/15) from 16 Medicine (A100) courses were analysed to identify data surrounding MLM sessions. This included: duration, format, title, and year of study, of any MLM components in the timetable. We also launched an anonymous online survey for medical students to determine their perceptions of MLM teaching in the curriculum. Across the timetables, 892 (range, 8–141) MLM teaching sessions were identified. Of these, 64.9% took place during clinical years. 644 medical students from 30 universities completed our survey. 88.3% agreed that MLM skills are important for junior doctors and 87.4% agreed that MLM is relevant to their education. Despite 57.5% agreeing that there should be specific standards set for graduating medical students, only 8.9% were aware of the Medical Leadership Competency Framework, and 17.1% felt that MLM is taught effectively in their curriculum. Students' preferences for teaching and assessment of MLM were not in line with the distribution of teaching sessions identified in our analysis, indicating that there are future challenges in matching student's expectations towards developing leadership capabilities with formalised undergraduate curricula. Medical students' teaching experience varies widely between universities, but the majority recognise the importance of MLM in their education and their future roles as junior doctors. This research provides novel insight into the national delivery of MLM within undergraduate medical schools, alongside important commentary on students' preferences for curriculum delivery. We anticipate that this research will be used to enhance teaching delivery and hope that this data is useful in supporting the leadership development of future doctors.